2023
DOI: 10.3390/ijms241210132
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and TGF-β-Secreting Adoptively-Transferred Murine Mesenchymal Stromal Cells Accelerate Healing of Psoriasis-like Skin Inflammation and Upregulate IL-17A and TGF-β

Abstract: Mesenchymal stromal cells (MSC) show promise as cellular therapeutics. Psoriasis is a chronic inflammatory disease affecting the skin and the joints. Injury, trauma, infection and medications can trigger psoriasis by disrupting epidermal keratinocyte proliferation and differentiation, which activates the innate immune system. Pro-inflammatory cytokine secretion drives a T helper 17 response and an imbalance of regulatory T cells. We hypothesized that MSC adoptive cellular therapy could immunomodulate and suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Although controversial data from in vivo studies have claimed that preconditioning MSCs with inflammatory cytokines is not essential for improvement in function in some inflammatory conditions [ 27 ], additional reports support the beneficial effect of the inflammatory stimulation of MSCs with IFN-γ [ 15 , 16 , 17 ], suggesting that the effect’s response could rely on different aspects, such as the kinds of cytokine, its concentration, and the kinds of cells. To our knowledge, no study has explicitly examined the in vitro effect of IFN-γ preconditioned hGMSCs on PBMC activation and maturation; therefore, this study first applied this strategy to evaluate and validate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although controversial data from in vivo studies have claimed that preconditioning MSCs with inflammatory cytokines is not essential for improvement in function in some inflammatory conditions [ 27 ], additional reports support the beneficial effect of the inflammatory stimulation of MSCs with IFN-γ [ 15 , 16 , 17 ], suggesting that the effect’s response could rely on different aspects, such as the kinds of cytokine, its concentration, and the kinds of cells. To our knowledge, no study has explicitly examined the in vitro effect of IFN-γ preconditioned hGMSCs on PBMC activation and maturation; therefore, this study first applied this strategy to evaluate and validate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…16 The upregulation of other cytokines, such as IL-6, IL-12, IL-22, IL-29, IL-36, IL-1 β, and tumor necrosis factorα, is also involved in the pathogenesis of psoriasis. [20][21][22][23][24][25] Among these cytokines, IL-6 is a pleiotropic cytokine involved in epithelial and immune cell angiogenesis, proliferation, and differentiation. [26][27][28][29] Owing to its excessive activation and dysregulation of receptor signaling in T cells, IL-6 is involved in the pathogenesis of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of other cytokines, such as IL‐6, IL‐12, IL‐22, IL‐29, IL‐36, IL‐1 β, and tumor necrosis factor‐α, is also involved in the pathogenesis of psoriasis 20–25 . Among these cytokines, IL‐6 is a pleiotropic cytokine involved in epithelial and immune cell angiogenesis, proliferation, and differentiation 26–29 .…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 , 16 recent research has shown that IL‐6 secreting MSC accelerates diabetes reversal through the upregulation of IL‐17A and TGF‐β in the skin. 17 Moreover, IL‐6 induces hyperproliferation and inflammation of cells, which is at least in part via the IL‐6/STAT3 (signal transducer and activator of transcription) signalling pathway, 18 a crucial signalling pathway identified in many diseases. 19 Importantly, in human keratinocytes, tripartite motif 27 (TRIM27) was found to be involved in the IL‐6/STAT3 signalling pathway by binding to PIAS3 and facilitating its ubiquitination.…”
Section: Introductionmentioning
confidence: 99%